Potential role of the gut microbiota in neuromyelitis optica spectrum disorder: Implication for intervention. (December 2020) - Cui, Chunping; Ruan, Yiwen; Qiu, Wei
Highlights: The important effects of gut microbiota on neuroimmunological diseases. Intestinal mucosal dysbiosis is associated with NMOSD. Microbiota intervention might be a potential therapeutic tool for treatment of NMOSD. Abstract: The gut microbiota plays an important role in the occurrence and development of neuroimmunological diseases. Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease of the central nervous system that is characterized by the peripheral production of the disease-specific serum autoantibody aquaporin-4 (AQP4)-IgG. Recently, accumulating evidence has provided insights into the associations of gut microbiota dysbiosis and intestinal mucosal barrier destruction with NMOSD, but the underlying pathogenesis remains unclear. Thus, a microbiota intervention might be a potential therapeutic strategy for NMOSD by regulating the gut microbiota, repairing the intestinal mucosal barrier, and modulating intestinal immunity and peripheral immunity.